Effects of Pectin and Modified Starch on the Properties of Gummy Candy from Pineapple Eye Juice - Nguyet T. M. Nguyen; Ngoc H. Han; Nhu T.H. Le; Oanh H.T. Le (Chemical Engineering Transactions)
In this work, pineapple eye juice (PEJ) was utilized to produce gummy candies (GC) to promote the development of a circular economy. The objective was to investigate the effects of pectin and modified starch (MS) on the structural properties and sensory qualities of GC made from PEJ. The method involved formulating GC with varying concentrations of pectin (0.05, 0.1, and 0.15 %) and MS (0.5, 1.0, and 1.5 %) alongside a constant 9 % gelatin concentration. Texture Profile Analysis (TPA) was employed to assess the textural properties, and the antioxidant activity was measured using the 2,2-diphenyl-1-picryhydrazyl (DPPH) radical scavenging method. The results demonstrated that a combination of 0.05 % pectin and 1.5 % MS yielded GC with a more stable structure, harmonious flavour, and better colour compared to formulations using fewer polymers. The antioxidant activity of these GC was determined to be 79.95 ± 0.2 %. The conclusion of this study highlights the potential for using PEJ by-products in GC production, offering a sustainable solution for the food system.